Prediction of Angiopoietin-like Protein 4-related Signaling Pathways in Cholangiocarcinoma Cells - Tin May Aung (2022)
Background/Aim: Angiopoietin-like protein 4 (ANGPTL4) is a multifunctional signaling protein implicated in carbohydrate metabolism, inflammation, cancer growth and progression, anoikis resistance, angiogenesis, and metastasis. However, signaling pathways of ANGPTL4 in cholangiocarcinoma (CCA) remain unknown. The aim of this study was to explore ANGPTL4-related signaling proteins and pathways associated with CCA biology. Materials and Methods: ANGPTL4 of CCA cells was silenced by small interfering RNA (siRNA) with scramble control and ANGPTL4-related signaling proteins were investigated using mass spectrometry, bioinformatics tools and molecular docking. Results: Among the 321 differentially expressed proteins, 151 were downregulated. Among them, bioinformatic analyses revealed that ANGPTL4 interacts with DNA-dependent protein kinase catalytic subunit (PRKDC) and 60S ribosomal protein L21 (RPL21) via AKT serine/threonine kinase 1 (AKT1), mechanistic target of rapamycin kinase (MTOR) and ribosomal protein L5 (RPL5). Online database analysis showed that mRNA and protein expression levels of ANGPTL4-related signaling proteins were significantly higher in CCA than in normal tissues. Moreover, a high mRNA expression level was associated with high tumor grade (p<0.0001) and lymph node metastasis (p<0.0001). Conclusion: The signaling pathway of ANGPTL4 in CCA progression might be regulated by PRKDC and RPL21. Furthermore, high expression of ANGPTL4-related signaling proteins has potential to be used in clinical prognosis.